Peran Penyuluh Agama Islam dalam Bimbingan Pelaksanaan Rukun Islam terhadap Keluarga Mualaf di Temanggung - Baedhowi; Heri Supriyanto Eko Putro; Fatmawati Sungkawaningrum (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2023)
The implementation of the pillars of Islam is a requirement for realizing a true Muslim, which is the hope of every family. Being able to practice the pillars of Islam in daily life is the dream of every Muslim family. This is especially true for converts (mualaf), as they need a mentor who consistently guides them in carrying out the pillars of Islam within their family. Based on the results of the research, the researcher concluded that the efforts made by the Religious Counselor of the Parakan District KUA in implementing the pillars of Islam for convert families include using face-to-face interview methods, followed by lectures, guidance through role modeling or demonstration, and finally, home visits.The implications of implementing the pillars of Islam for convert families, when linked to the functions of religious counseling, show that it effectively helps converts understand the practice of the pillars of Islam, particularly among convert families in Traji Village, Parakan District, Temanggung Regency.